2020
DOI: 10.1016/j.eclinm.2020.100547
|View full text |Cite
|
Sign up to set email alerts
|

An open-label, randomized trial of the combination of IFN-κ plus TFF2 with standard care in the treatment of patients with moderate COVID-19

Abstract: Background Epidemic outbreaks caused by SARS-CoV-2 are worsening around the world, and there are no target drugs to treat COVID-19. IFN-κ inhibits the replication of SARS-CoV-2; and TFF2 is a small secreted polypeptide that promotes the repair of mucosal injury and reduces the inflammatory responses. We used the synergistic effect of both proteins to treat COVID-19. Methods We conducted an open-label, randomized, clinical trial involving patients with moderate COVID-19.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Nebulized IFN was also shown to decrease mortality in COVID‐19 patients in other studies 38,39 . Fu et al 40 showed that nebulized IFN‐k plus trefoil factor 2 (TFF2) was associated with clinical improvement in COVID‐19 patients and their consequent early discharge from hospital. A study involving about 100 COVID‐19 patients (NCT04385095) reported that nebulized IFN‐β1a might be highly effective, with a 79% lower risk of developing severe disease.…”
Section: Nebulized Ifn Treatment For Covid‐19mentioning
confidence: 90%
“…Nebulized IFN was also shown to decrease mortality in COVID‐19 patients in other studies 38,39 . Fu et al 40 showed that nebulized IFN‐k plus trefoil factor 2 (TFF2) was associated with clinical improvement in COVID‐19 patients and their consequent early discharge from hospital. A study involving about 100 COVID‐19 patients (NCT04385095) reported that nebulized IFN‐β1a might be highly effective, with a 79% lower risk of developing severe disease.…”
Section: Nebulized Ifn Treatment For Covid‐19mentioning
confidence: 90%
“…Safety concerns were raised by one of the studies with increased liver enzymes in leflunomide-treated patients. 70 IFN-alpha 71 and IFN-kappa 72 reduced the time to negative conversion of SARS-CoV-2 in two studies. Two prospective studies on baricitinib at high RoB provided conflicting results for every assessed outcome and only agreed on the fact that addition of baricitinib to SOC did not worsen the safety profile of the therapeutic strategy.…”
Section: Other Immunomodulatory Drugsmentioning
confidence: 93%
“…It has been demonstrated that early administration of type I IFNs inhibits viral replication in vitro by partially restoring innate immune response to SARS-CoV-2 infection [ 156 ]. A randomized clinical trial of 80 patients with moderate COVID-19 and pneumonia found that aerosol inhalation of IFN-ĸ (a type I IFN) combined with TFF2 anti-inflammatory polypeptide led to faster SARS-CoV-2 clearance and facilitated clinical resolution of pneumonia [ 199 ]. A phase 2 clinical trial assessing the efficacy of IFN-β (a type I IFN) treatment in 127 COVID-19 patients found that IFN-β in combination with lopinavir-ritonavir and ribavirin shortened viral shedding time and hospital stay [ 200 ].…”
Section: Therapeutic Strategies For Sars-cov-2-mediated Endotheliamentioning
confidence: 99%